Evaluating Financial Risk and Pricing Accuracy Using Full Costing: A Case Study on UMKM Tempe Mbak Novi in Purworejo - Abbas, Yeni Elfiza; Asmilia, Nur; Handayani, Murnaningsih Wahyu (Yayasan Pendidikan Penelitian Pengabdian Al-amsi, 2025)
This study evaluates the financial risk implications of pricing inaccuracy and analyzes the effectiveness of the full costing method in improving financial decision-making within small enterprises. Using a case study of UMKM Tempe Mbak Novi in Purworejo, Indonesia, the research integrates cost accounting with financial risk evaluation to assess how incomplete cost allocation affects profitability, liquidity, and cash flow stability. Data were collected through interviews, observations, and documentation. Results show that the firm’s cost-of-production calculation underestimates total costs by IDR 4,074,000 compared to the full costing approach. This mispricing leads to a potential profit loss of 24.1% and increases financial risk exposure, particularly cash flow volatility and underpricing risk. The findings suggest that implementing a full costing system enables more accurate pricing, strengthens financial sustainability, and reduces operational risk for micro and small enterprises